Notch signaling facilitates crossing of endothelial barriers by tumor cells - Rodriguez-Vita, Juan; Fischer, Andreas (Molecular & cellular oncology, 2017)
Blood vessels supply tumor cells with oxygen and nutrients and provide the basis for metastatic dissemination. In addition, endothelial cells can provide factors that orchestrate the behavior of tumor cells. Here, we expand upon our previous findings that link activation of Notch signaling in the endothelium to cellular senescence, weakening of cell junctions, and expression of adhesion molecules, which facilitates tumor and immune cell migration across the vessel wall and homing at distant sites.
Gesehen am 23.07.2018